An Intimate Partner Violence (IPV) Protocol Readiness Model. (April 2014) - Daire, Andrew P.; Carlson, Ryan G.; Barden, Sejal M.; Jacobson, Lamerial
Intimate partner violence (IPV) is a widespread, pervasive issue that affects heterosexual and same-sex relationships. However, IPV is largely underreported, and many counselors do not formally assess for relationship violence. Additionally, counselors typically do not have a plan to manage disclosures of violence when they occur. We present an IPV Protocol Readiness Model that helps counselors determine their readiness to assess for IPV as well as manage disclosures. Additionally, we present a questionnaire intended to provide guidance for counselors regarding organizational and community factors important to the success of an IPV protocol. Finally, we discuss practical applications and suggestions for further research.